The leader's edge : - Hale, Guy A. (Irwin Professional Pub., 1996)
The men and women who will get ahead in the next decase won't necessarily be harder-working, more motivated, smarter, or even more experienced. Instead, they will think better. Learning how to think, especially in these rapidly changing times, will unlock doors that talent, motivation, and experience alone can't. The Leader's Edge provides the tools to master the ``art'' of thinking as well as the confidence to handle any business decision. Providing practical skills rather than philosophy along, The Leader's Edge instructs readers on the five skills needed to think more accurately: situation review; cause analysis; decision making; plan analysis; innovation.